VARIANTS OF CLINICAL COURSE OF COMMUNITY-ACQUIRED PNEUMONIA IN CHILDREN OF DIFFERENT AGES - Sharipov I.L. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Pneumonia is a serious disease characterized by inflammation in the lungs. In children, this disease often runs especially hard due to the immaturity of the respiratory apparatus as well as the inability to fully expectorate sputum. Pathology requires mandatory prescription of antibiotics and symptomatic drugs, and in severe cases, hospitalization.